Study on Low Carbon Tourism Model at Ancient Town of Si Thep, a World Heritage City, Thailand - Kingkanok Saowapawong; Tiwawan Siricharoen Kanha; Krittika Saynaratchai; Thanapat Mongkolthanachok; Phongthep Hanpattanakit (Chemical Engineering Transactions)
Low carbon tourism reflects the degree of environmental concern within the tourism industry and serves as the foundation for green, sustainable, and ecological tourism. There is a lack of clear strategies and understanding in transforming tourist areas, especially world heritage sites, into low carbon tourism destinations. An example is Si Thep Historical Park in Phetchabun province, a significant center of civilization in Thailand. The objectives of this study were to estimate the greenhouse gas (GHG) emission and analyse the potential of tourism resources around Si Thep World Heritage sites for low carbon tourism in Thailand. The results found that the total GHG emission from sewage, fossil fuel burning, electricity, and solid waste at Si Thep Historical Park for 2023 were 817,009 kg CO2eq yr-1. Most of the GHG emissions were from sewage and fossil fuel burning for tourist transportation in the area. The highest GHG emissions occurred during September to December 2023, ranging from 93,485 to 164,767 kg CO2eq month-1. The total number of tourists in 2023 was 685,716 persons, with GHG emissions per person amounting to 1.19 kg CO2eq. A SWOT analysis of tourism resources at Si Thep Historical Park revealed strong potential for managing low carbon tourism. The SWOT analysis revealed significant strengths in community engagement and natural resources, but also highlighted weaknesses in infrastructure and external threats from climate change. This study contributes by setting objectives to initiate GHG evaluations and analyse the potential of tourism resources around Si Thep World Heritage sites to develop a low carbon tourism model in Thailand.